The house is on fire - Beanland, Rachel (Simon & Schuster, 2023)
Told from the perspectives of four people whose actions changed the course of history, this masterful work of historical fiction takes readers back to 1811 Richmond, Virginia, where, on the night after Christmas, the city's only theater burned to the ground, tearing apart a community.